The Concept of Semantic Phase and the Different Readings of ’again’ - Gründer, Sabine (Proceedings of Sinn und Bedeutung, 2019)
The paper offers a new kind of approach to the semantic contrast between repetitive and restitutive again. The heart of the theory is the new concept of Semantic Phase. It parallels the syntactic concept and is motivated as an instance of the Principle of Hierarchical Abstraction. The concept refers to a switch from imperfective to perfective view of a situation at the level of vP. Applying the modifier before or after phase transition derives the two readings without stipulation of lexical ambiguity. The framework used is Finite-state Temporal Semantics of Fernando. The syntactic background is an Orphan analysis of right-peripheral adverbials. Syntactic underspecification is resolved by the use of pragmatic information reflected locally by the prosody of the utterance.